2017
DOI: 10.1111/1365-2664.12847
|View full text |Cite
|
Sign up to set email alerts
|

Density‐dependent vulnerability of forest ecosystems to drought

Abstract: 1. Climate models predict increasing drought intensity and frequency for many regions, which may have negative consequences for tree recruitment, growth and mortality, as well as forest ecosystem services. Furthermore, practical strategies for minimizing vulnerability to drought are limited. Tree population density, a metric of tree abundance in a given area, is a primary driver of competitive intensity among trees, which influences tree growth and mortality. Manipulating tree population density may be a mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
154
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 253 publications
(167 citation statements)
references
References 53 publications
10
154
2
1
Order By: Relevance
“…One caveat to this is that mean predicted loblolly weather mortality was consistently underestimated each year (i.e., observations were 29-66% greater than predictions across all years; Appendix S1: Fig. Recent tree-ring studies of pine species across the U.S. highlight the effectiveness of thinning and reduced stand densities at mitigating water stress (D'Amato et al 2013, Bottero et al 2017, Gleason et al 2017) lending support to our observations in east Texas. Despite this, observed mean loblolly pine weather mortality and standard errors were consistently lower than other species.…”
Section: Discussionsupporting
confidence: 63%
“…One caveat to this is that mean predicted loblolly weather mortality was consistently underestimated each year (i.e., observations were 29-66% greater than predictions across all years; Appendix S1: Fig. Recent tree-ring studies of pine species across the U.S. highlight the effectiveness of thinning and reduced stand densities at mitigating water stress (D'Amato et al 2013, Bottero et al 2017, Gleason et al 2017) lending support to our observations in east Texas. Despite this, observed mean loblolly pine weather mortality and standard errors were consistently lower than other species.…”
Section: Discussionsupporting
confidence: 63%
“…This would again suggest that critical to understanding the effects of drought on growth is factoring in not just the occurrence, but also the timing, duration and intensity of drought events, as well as the local adaptation or preconditioning of trees to drought. In addition to this, another factor that could have contributed to the strong drought response in Romania is the high basal area of the stands at this site (Table 1), which previous work has shown can modulate the impact of drought on forest growth by exacerbating belowground competition for water (Bottero et al 2017). …”
Section: Discussionmentioning
confidence: 90%
“…A number of studies have demonstrated the interactions between competition and climate variables (Bottero et al., ), but the mechanisms are still poorly understood (Grant, Tague, & Allen, ; Thomas & Waring, ). In our analyses, only the summer soil moisture deficit for P. sylvestris interacted with competition, and so that stronger tree–tree competition ameliorated the negative effects of summer drought.…”
Section: Discussionmentioning
confidence: 99%